Do people’s perceptions and attitudes associate with enrollment in health insurance in a context of Nepal? - Acharya, Devraj; Devkota, Bhimsen; Bhattarai, Radha (Nepalese Journal of Insurance and Social Security, 2021)
The Government of Nepal introduced the health insurance [HI] program in three districts, in 2016 and now has been expanded almost all districts. Since it was a new initiative, there was no clear evidence on people's attitude, perception, and awareness, which continues until now. This study, therefore, intended to assess the perception and attitude of household heads towards enrollment in HI. The descriptive research design was used and 810 households in Baglung and Kailali Districts of Nepal were selected randomly. The interview schedule used for data collection comprised positive and negative statements at a three-point scale as independent variables to explore the perception and attitude of people towards HI and enrollment in HI as a dependent variable. Most of the respondents agreed with the statement where attitude and perception were significantly associated with the enrollment in HI. Among the 16 statements, 13 statements were observed statistically significant. Among them: 'anyone can enroll easily in HI', 'primary service point is appropriate', 'contribution amount is appropriate', 'coverage amount is appropriate', 'HI may solve the problem', 'proper dissemination of information, education, communication [IEC] materials may help to enroll', 'health services quality has not been improved after enrollment', 'IEC materials are not appropriate', 'HI related queries are addressed timely', 'relatives/neighbors do/did not request me to enroll', 'complaints are not addressed timely', and 'information is not adequate' were the significantly associated for enrollment in HI. The perception and attitude of the household heads were significantly associated with the enrollment in HI. The study recommends an appropriate IEC campaign for positive perception and attitudes that leads to better participation in HI. The policymaker may consider the findings while planning the program intervention.